Pathway-Based Analysis of Genome-Wide Association Data Identified SNPs in HMMR as Biomarker for Chemotherapy- Induced Neutropenia in Breast Cancer Patients - Bidadi, Behzad; Liu, Duan; Kalari, Krishna R.; Rubner, Matthias; Hein, Alexander; Beckmann, Matthias W.; Rack, Brigitte; Janni, Wolfgang; Fasching, Peter A.; Weinshilboum, Richard M.; Wang, Liewei (Frontiers in Pharmacology, 2018)
Neutropenia secondary to chemotherapy in breast cancer patients can be life-threatening and there are no biomarkers available to predict the risk of drug-induced neutropenia in those patients. We previously performed a genome-wide association study (GWAS) for neutropenia events in women with breast cancer who were treated with 5-fluorouracil, epirubicin and cyclophosphamide and recruited in the SUCCESS-A trial. A genome-wide significant SNP signal in the tumor necrosis factor superfamily member 13B (TNFSF13B) gene, encoding the cytokine B-cell activating factor (BAFF), was identified in that GWAS. Taking the advantage of these existing GWAS data, in the present study, we utilized a pathway-based analysis approach by leveraging the knowledge of pharmacokinetics and pharmacodynamics of drugs and breast cancer pathophysiology to identify additional SNPs/genes and underlying etiology of the chemotherapy-induced neutropenia. We identified three SNPs in the hyaluronan mediated motility receptor (HMMR) gene that were significantly associated with neutropenia (p < 1.0E-04). Those three SNPs were trans-eQTLs for expression of TNFSF13B (p <1.0E-04). The minor allele of these HMMR SNPs was associated with a decreased TNFSF13B mRNA level. Additional functional studies performed with the lymphoblastoid cell lines (LCLs) demonstrated that LCLs possessing the minor allele of HMMR SNPs were more sensitive to drug treatment. Knock-down of TNFSF13B in LCLs and HL-60 promyelocytic cells and treatment of those cells with BAFF modulate the cell sensitivity to chemotherapy treatment. These results demonstrate that HMMR SNP-dependent cytotoxicity of these chemotherapeutic agents might be related to the TNFSF13B expression level. In summary, utilizing a pathway-based approach for analysis of GWAS data, we identified additional SNPs in the HMMR gene were associated with neutropenia that were also correlated with TNFSF13B expression.